Candida Esophagitis: A Retrospective Study of Upper Gastrointestinal Endoscopic Grading and the Characteristic Profile - Steven Sumantri; Marcellus Simadibrata; Moch Ikhsan Mokoagow; Deddy Gunawanjati; Seri Mei Maya Ulina; Bona Adhista; Novie Rahmawati Zirta; Riahdo Saragih; Daldiyono Daldiyono; Abdul Aziz Rani; Murdani Abdullah; Ari Fahrial Syam; Chudahman Manan; Dadang Makmun; Achmad Fauzi (The Indonesian Society for Digestive Endoscopy, 2011)
Background: Candida esophagitis is a common abnormality found on esophagogastroduodenoscopy (EGD) procedure in patients with recognizable risk factors. However, the finding is frequently incidental as most of them are asymptomatic. There has been no study on the characteristics of Candida esophagitis in Indonesia. The aim of this study was to describe the degree of Candida esophagitis and its characteristics in patients who underwent EGD procedure at Cipto Mangunkusumo Hospital. Method: A retrospective study was conducted on all EGD procedures at the Gastroenterology Procedure Room, Internal Medicine Department, Cipto Mangunkusumo Hospital, between January 2007 and December 2009 with a total of 2,311 samples. The study was carried out by visually examining all endoscopic procedures and grading them according to the Kodsi severity grading (1976), and evaluating medical records. Data analysis was performed using Microsoft Excel 2007. Results: During the study period, Candida esophagitis was found in 2.6% patients with predominant male (68.9%) and the average age was 49.8 ± 15 years. The chief complaints found were dyspepsia (34.4%), melena (21.3%) and dysphagia (4.9%) and 32.8% patients were asymptomatic. The most frequent risk factors were age ≥ 60 years old (28.3%), proton pump inhibitor or H2 receptor antagonist user (26.4%), and antibiotics (17.0%). Grade II Kodsi candidiasis was the most prevalent degree in this study (44.3%). Conclusion: Candida esophagitis was one frequent finding in endoscopy based on the complaint of dyspepsia in patients with certain risk factors. However, the results of this study still need further validation in prospective studies. Keywords: Candida esophagitis, esophagogastroduodenoscopy, risk factors, grading